Stable and Easily Accessible Functional Dyes: Dihydrotetraazaanthracenes as Versatile Precursors for Higher Acenes. Issue 20 (7th April 2015) - Gampe, Dominique Mario; Kaufmann, Martin; Jakobi, Dörthe; Sachse, Torsten; Presselt, Martin; Beckert, Rainer; Görls, Helmar
Abstract A series of new dihydrotetraazaanthracenes and one new dihydrotetraazatetracene as substances for applications in organoelectronic devices and as suitable building blocks for higher azaacenes was synthesised. The condensation of aromatic diamines with dichlorodicyanopyrazine led to these tricyclic/tetracyclic compounds. Syntheses of N‐substituted phenylenediamines were developed to enable the introduction of multiple functional groups such as ester, amino, or nitro groups on the chromophoric system. Relationships between the structure and the spectroscopic properties could be derived from UV/Vis absorption and fluorescence spectroscopy, as well as by DFT and TD‐DFT calculations of molecular and aggregate structures. The absorption spectra are dominated by π–π* transitions of the single molecules, whereas aggregation needs to be taken into account to obtain reasonable agreement between theory and experiment in certain cases. Single‐crystal X‐ray analyses were carried out to examine the morphology and solid packing effects. Finally, a dihydrotetraazaanthracene was used as a building‐block to create a mesoionic octaazapentacene.